EFFECT OF SUPPLEMENTATION OF DETOXIFIED MATRI FLOUR WITH WHEAT FLOUR ON THE QUALITY OF pAN BREAD - Lodhi, Salman Ahmad; Rehman, Salim-ur-; Huma, NuzJhat (Biological Sciences - PJSIR, 2003)
Breads were prepared from wheat flour supplemented with 5, 10, 15, 20 and 25% of detoxified matri flour and evaluated for sensory acceptability, i.e. bread taste, aroma, texture, crumb colour, grain, loaf volume, crust colour, symmetry of form, character of crust and evenness of bake. Brabender farinograph, mixograph and viscoarnylograph characteristics of flour were also studied. Farinograph water absorption, arrival time and dough development time increased and dough stability decreased and amylograph peak viscosities, mixograph peak height and mixing time decreased as level of supplementation with matri flour increased. The quantities of crude protein, crude fibre, crude fat and ash increased with the increase of matri flour in wheat flour. Increasing levefs of legume substitution decreased many sensory parameters of wheat bread. Results indicate that detoxified matri flour can successfully be substituted for wheat flour in breads at levels up to 10% . Legume substitution tended to increase the protein level in the finished product.